2007
DOI: 10.1002/jbm.b.30805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of regional bond strength in root thirds among fiber‐reinforced posts luted with different cements

Abstract: Highest bond strength values were obtained in the cervical third and with resin cements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 43 publications
(61 reference statements)
4
53
3
2
Order By: Relevance
“…Despite the methodological differences, previous studies (2,3,20,(22)(23)(24) have also verified higher bond strength in the coronal root canal region. Analysis of the failure modes confirm the lower values of adhesion in the apical region, with predominance of adhesive and mixed-type failures in this region.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the methodological differences, previous studies (2,3,20,(22)(23)(24) have also verified higher bond strength in the coronal root canal region. Analysis of the failure modes confirm the lower values of adhesion in the apical region, with predominance of adhesive and mixed-type failures in this region.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies also showed highest bond strength to cervical third. 9,22 Other factors, such as difficult access to the apical region and possible limitations of cement flow may be assigned for this result, 12,22 as well as the decreasing effectiveness of light curing at regions farther from the light source, since that the performance of the dual-cured resin cements improve after setting by light and chemical activation; demonstrating the importance of light curing. 12,22,23 No significant difference was found between the root thirds of fiber posts cemented with self-adhesive cements.…”
Section: Resultsmentioning
confidence: 85%
“…3 They distribute the occlusal stress more uniformly along the root, leading to lower occurrence of root fractures. 4 However, the cementation of GFP is a sensitive technique and some variables may impair the bond between cement and dentin, such as the several materials used for endodontic treatment, [5][6][7] root canal morphological variations, 8,9 control of dentin moisture, formation of bubbles in the resin cement and difficult curing of the resin cement at the middle and apical root thirds. [5][6][7][8][9][10][11][12] Therefore, a successful treatment requires good bonding between…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be associated with the cement used in this study (RelyX U100), which has high viscosity and, therefore, does not reach the apical third in some cases [38,39]. Furthermore, an adequate polymerization is necessary to achieve satisfactory mechanical properties.…”
Section: Discussionmentioning
confidence: 97%